Emergence of mcr-8.2-mediated colistin resistance in Klebsiella pneumoniae isolated from pediatric diarrhea cases in southern Vietnam - Nga Thi Le; Phuong Hoai Hoang; Quynh Nguyen; Minh Nhat Ha Truong; Chinh Van Dang; Tinh Huu Ho; Phuc Le Hoang; Dinh Quang Truong; Ha Thi Thanh Nguyen; Chuong Van Le; Trang Thi Phuong Phan (Journal of Global Antimicrobial Resistance)
Background: Colistin resistance poses a growing global challenge, particularly in low- and middle-income countries where antibiotic misuse is prevalent. This study investigates the prevalence of colistin resistance in Klebsiella spp. and characterizes the genetic features of resistant isolates, focusing on the mcr-8.2 gene identified in a Klebsiella pneumoniae isolate from pediatric diarrheal cases in southern Vietnam. Methods: Stool samples were collected from 500 pediatric patients (aged 0–5 years) hospitalized with diarrhea in two tertiary hospitals in Ho Chi Minh City between March and September 2022. Samples were cultured on Violet Red Bile Glucose Agar, then presumptive Klebsiella spp. colonies were selected, purified on nutrient agar, and identified using MALDI-TOF MS. Colistin resistance was determined via minimum inhibitory concentration testing, and the presence of mcr genes was confirmed through polymerase chain reaction. Whole-genome sequencing was performed on the Klebsiella pneumoniae strain harboring mcr-8.2 to elucidate resistance mechanisms. Strain characterization was performed using multi-locus sequence typing, while conjugation experiments assessed horizontal gene transfer potential. Results: Among 121 Klebsiella spp. isolates, 49 (40.5%) were resistant to colistin. The mcr-1 gene was detected in 31 isolates (25.6%), whereas the mcr-8 was identified in a single isolate (0.8%), with a colistin MIC of 16 µg/mL. Genomic analysis revealed 34 antibiotic resistance genes, including mcr-8.2 and multiple β-lactamase genes, alongside plasmid types IncFIB and IncFII. Chromosomal mutations in phoP, phoQ, and lpxM were also implicated in colistin resistance. Conclusions: This study documents the emergence of mcr-8.2-mediated colistin resistance in K. pneumoniae from pediatric diarrhea in Vietnam and highlights a high prevalence of multidrug resistance in Klebsiella spp.. Continuous surveillance of mcr genes and novel therapeutic strategies are urgently needed.